Daily mobility in Brussels: challenges, tools and priority undertakings - Michel Hubert; Kevin Lebrun; Philippe Huynen; Frédéric Dobruszkes (Brussels Studies)
This synopsis makes use of the data and analyses from the first two Cahiers de l’Observatoire de la mobilité of the Brussels-Capital Region, bringing up to date the synopsis from the Citizens’ Forum of Brussels published in 2009 and adding to it considerably. It provides a complete and detailed overview of this matter, which represents one of the Region’s key responsibilities and expenses. The first part of the synopsis presents the main challenges which Brussels faces. It then looks at the tools and institutional challenges (the means of action are particularly complex in Brussels and the balance of powers between stakeholders is formidable), before ending with an analysis of the convergences and divergences surrounding two undertakings which many feel are a priority for Brussels: the development of the railway network of the Société des Transports Intercommunaux Bruxellois (STIB) and the operating of the future RER.